2017
DOI: 10.1155/2017/7602951
|View full text |Cite
|
Sign up to set email alerts
|

Transit-Amplifying Cells in the Fast Lane from Stem Cells towards Differentiation

Abstract: Stem cells have a high potential to impact regenerative medicine. However, stem cells in adult tissues often proliferate at very slow rates. During development, stem cells may change first to a pluripotent and highly proliferative state, known as transit-amplifying cells. Recent advances in the identification and isolation of these undifferentiated and fast-dividing cells could bring new alternatives for cell-based transplants. The skin epidermis has been the target of necessary research about transit-amplifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 92 publications
(125 reference statements)
0
44
0
Order By: Relevance
“…Since epidermal stratification involves delamination and asymmetrical cell division of basal cells [ 7 , 8 ], and we observed a higher percentage of K14 positive cells in the suprabasal layers of the p130CasKO, we hypothesized that p130Cas deletion might impact progenitor cells commitment toward differentiation. Consistently, we found that freshly isolated p130CasKO primary keratinocytes have an overall reduced clonogenic capacity with a strong reduction of colonies displaying holoclone- and meroclone-like morphology, which was also maintained in second-generation clonogenic assays (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since epidermal stratification involves delamination and asymmetrical cell division of basal cells [ 7 , 8 ], and we observed a higher percentage of K14 positive cells in the suprabasal layers of the p130CasKO, we hypothesized that p130Cas deletion might impact progenitor cells commitment toward differentiation. Consistently, we found that freshly isolated p130CasKO primary keratinocytes have an overall reduced clonogenic capacity with a strong reduction of colonies displaying holoclone- and meroclone-like morphology, which was also maintained in second-generation clonogenic assays (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the epidermis, the stem cell compartment undergoes asymmetrical cell division generating committed, differentiating progenitor cells that are further subjected to few rounds of cell division after which they undergo terminal differentiation by moving upward [ 8 , 30 ]. The prerequisite to generate these progenitor cells is loss of integrin-based adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a transit amplifying (TA) population in the germ line has been contentious. TA cells are stem cell progeny that have left the niche but have not yet differentiated and instead continue to undergo some number of mitotic divisions before differentiating [ 106 , 107 ]. Experiments using emb-30 mutants blocked for the metaphase-to-anaphase transition at the restrictive temperature show that a distal 6–8 rows of germ cells arrest in metaphase and fail to acquire markers of differentiation as rapidly as more proximal germ cells in the PZ [ 95 ]; the more proximal cells also rapidly enter meiosis upon refeeding after starvation [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in tissues the cellular metabolic pathways utilized for growth and function largely depend on the proliferative nature of the cell type. As mentioned above, the colon and small intestine contain both highly proliferative stem cells and transit-amplifying progenitor population and post-mitotic differentiated cells (48). The post-mitotic differentiated cells have a high rate of energy expenditure due to energy-consuming digestive, secretory, and absorptive processes (49).…”
Section: Hypoxia and Intestinal Cellular Metabolismmentioning
confidence: 99%